2021
DOI: 10.3934/neuroscience.2022002
|View full text |Cite
|
Sign up to set email alerts
|

Gut neurotoxin p-cresol induces brain-derived neurotrophic factor secretion and increases the expression of neurofilament subunits in PC-12 cells

Abstract: <abstract> <p>Increased p-cresol levels reportedly alter brain dopamine metabolism and exacerbate neurological disorders in experimental animals. In contrast to toxic concentrations, low doses of p-cresol may have distinct effects on neuronal metabolism. However, the role of p-cresol in synapse remodeling, neurite outgrowth, and other anabolic processes in neurons remains elusive. We propose that low doses of p-cresol affect neuronal cell structural remodeling compared with the high concentration-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Furthermore, our observations align with our earlier work (Tevzadze, 2020; Tevzadze 2019), indicating the influence of p-cresol on N-methyl-D-aspartate (NMDA) receptors. Specifically, it was noted that the content of the NR2B subunit of NMDA glutamate receptors increased in rats treated with p-cresol.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our observations align with our earlier work (Tevzadze, 2020; Tevzadze 2019), indicating the influence of p-cresol on N-methyl-D-aspartate (NMDA) receptors. Specifically, it was noted that the content of the NR2B subunit of NMDA glutamate receptors increased in rats treated with p-cresol.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study by the authors using rat pheochromocytoma cells (PC-12 cells) demonstrated the effects of p-cresol on the secretion of BDNF and neurofilament subunit expression (17). Low doses of p-cresol enhanced BDNF secretion and nerve growth factor induced the differentiation in PC-12 cells in culture.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that oral vancomycin treatment causes a considerable improvement in the symptoms of patients with ASD (15,16). In a recent study, the authors found that a low concentration of p-cresol, compared with a high concentration, potentiates nerve growth factorinduced differentiation via the secretion of brain-derived neurotrophic factor (BDNF) in cultured PC-12 cells, demonstrating that low doses of p-cresol, in contrast to a high toxic dose, can affect neuronal cell structural remodeling (17). The present study examined the effects of vancomycin on the behavioral responses of rats in open-field tests and novel object recognition tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary p-cresol and CS have been found elevated in ASD-diagnosed children < 8 years (Altieri et al, 2011; Persico & Napolioni, 2012). Animal models have shown that CS is a gut derived neurotoxin that can impact neuronal cell structural remodeling even at low doses via oxidative stress and secretion of brain-derived neurotrophic factor (Tevzadze et al, 2022). Indeed, p-cresol might impact developmental processes since it is related to impaired dendritic development, synaptogenesis, and synapse function in hippocampal neurons, which are crucial for cognitive and neural development in children (Guzmán-Salas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%